HARNESSING GAME-BASED TOOLS IN EFL CLASSROOMS: MGMP TEACHERS’ PERSPECTIVES ON USING KAHOOT - Heridayani, Heridayani; Hasibuan, Selamat Husni; Wariyati, Wariyati (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study explores how English teachers in an Indonesian MGMP (Musyawarah Guru Mata Pelajaran) community perceive and integrate Kahoot in EFL classrooms. Using a descriptive qualitative design, data were collected from six teachers through interviews, classroom observations, and document analysis. The results show that teachers use Kahoot for various pedagogical purposes, including vocabulary review, grammar reinforcement, and formative assessment. Teachers also employed different integration strategies, using Kahoot as warm-ups, comprehension checks, and review activities. Despite challenges such as limited internet access, lack of devices, and time constraints, teachers observed significant improvements in student motivation, participation, and confidence. The study highlights the role of professional collaboration within MGMP in supporting technology use, and the importance of teacher agency in adapting digital tools to meet classroom needs. The findings suggest that teacher-mediated gamification through Kahoot can enhance both engagement and learning outcomes in EFL contexts, particularly when supported by reflective teaching practices and local collaboration.